Investigation on the effect of moisture induced damage on asphaltic concrete mix incorporating waste concrete aggregates - Juraidah, Ahmad; Ekarizan, Shaffie; Norfarah Nadia, Ismail; Haryati, Awang; Masyitah, Md Nujid (Institute of Physics, 2023)
Recycling waste materials, such as partial replacement of WCA for natural aggregates in hot-mix asphalt, could be an option for addressing problems such as environmental pollution and the increasing demand for natural resources. Due to continual development and renovation in the construction industry, the generation of concrete waste has become one of the major challenges. Consequently, the purpose of this study was to develop an asphalt mix design utilizing waste concrete aggregate (WCA) as a partial substitute for natural aggregates (NA). The ratios of WCA10:NA90 and WCA30:NA70 are utilised to design the asphalt mixtures. In this study, asphalt mixtures containing 10 and 30 percent WCA are referred as WCA10 and WCA30, respectively. The density-voids analysis enables the determination of the optimum asphalt content that satisfies the criteria of the Malaysian Public Works Department (PWD). Results indicates that the criteria and design parameters of both mix conforms to the PWD specifications. The optimum asphalt content determined for both WCA10 and WCA30 asphalt mix is 5.7 and 5.8 percent respectively. The moisture sensitivity test is then performed on both WCA10 and WCA30 asphalt mixtures to determine how susceptible these mixtures are to moisture-induced damage. The tensile strength ratio (TSR) for WCA10 and WCA30 asphalt mixtures is 83.6 and 97.4 percent, respectively, which is greater than the minimal requirement of 80%. This investigation revealed that the use of WCA in hot-mix asphalt satisfies the moisture susceptibility requirements.